Methicillin-susceptible and Methicillin-resistant Staphylococcus aureus Bacteremia: Nationwide Estimates of 30-Day Readmission, In-hospital Mortality, Length of Stay, and Cost in the United States. (11th February 2019) - Inagaki, Kengo; Lucar, Jose; Blackshear, Chad; Hobbs, Charlotte V
Abstract: Background: Information on outcomes of methicillin-susceptible and -resistant Staphylococcus aureus (MSSA and MRSA, respectively) bacteremia, particularly readmission, is scarce and requires further research to inform optimal patient care. Methods: We performed a retrospective analysis using the 2014 Nationwide Readmissions Database, capturing 49.3% of US hospitalizations. We identified MSSA and MRSA bacteremia using International Classification of Diseases, Ninth Revision, Clinical Modification among patients aged ≥18 years. Thirty-day readmission, mortality, length of stay, and costs were assessed using Cox proportional hazards regression, logistic regression, Poisson regression, and generalized linear model with gamma distribution and log link, respectively. Results: Of 92 089 (standard error [SE], 1905) patients with S. aureus bacteremia, 48.5% (SE, 0.4%) had MRSA bacteremia. Thirty-day readmission rate was 22% (SE, 0.3) overall with no difference between MRSA and MSSA, but MRSA bacteremia had more readmission for bacteremia recurrence (hazard ratio, 1.17 [95% confidence interval CI, 1.02–1.34]), higher in-hospital mortality (odds ratio, 1.15 [95% CI, 1.07–1.23]), and longer hospitalization (incidence rate ratio, 1.09 [95% CI, 1.06–1.11]). Readmission with bacteremia recurrence was particularly more common among patients with endocarditis, immunocompromising comorbidities, and drug abuse. The cost of readmission was $12 425 (SE, $174) per case overall, and $19 186 (SE, $623) in those with bacteremia recurrence. Conclusions: Thirty-day readmission after S. aureus bacteremia is common and costly. MRSA bacteremia is associated with readmission for bacteremia recurrence, increased mortality, and longer hospitalization. Efforts should continue to optimize patient care, particularly for those with risk factors, to decrease readmission and associated morbidity and mortality in patients with S. aureus bacteremia. Abstract : Thirty-day readmission after having Staphylococcus aureus bacteremia is common and costly. Methicillin-resistant S. aureus bacteremia is associated with readmission for recurrent bacteremia, mortality, and longer hospitalization. Identifying high-risk patients for readmission may help optimize care for S. aureus bacteremia.